Presupposition in the Documentary Ice Cold: Murder, Coffee, and Jessica Wongso: A Forensic Linguistic Study - Abdul Muntaqim Al Anshory; Ghana Aldila Septiani (Master Program in Linguistics, Diponegoro University, 2025)
In 2016, Indonesia was captivated by the sensational cyanide murder case involving Mirna Salihin and Jessica Wongso, which resurfaced in 2023 through Netflix’s documentary Ice Cold: Murder, Coffee, and Jessica Wongso. While public discourse focused on the legal drama, little attention has been given to the linguistic mechanisms shaping perception within such forensic narratives. This study addresses that gap by examining how presuppositions construct meaning and potential bias in the documentary’s discourse. Utilizing George Yule’s presupposition theory within a forensic linguistic framework, the research identifies and categorizes presupposition types embedded in the dialogues. The study applies a qualitative method, collecting fifteen data samples through observation and note-taking of segments containing presuppositional cues. The analysis reveals the presence of 8 existential, 7 factive, 2 lexical, 4 non-factive, 3 counterfactual, and 1 structural presupposition, which indicate that the allegation of murder committed by Jessica Wongso against Mirna Salihin remains inconclusive. These linguistic patterns suggest how narrative framing and implied assumptions may influence audience interpretation of guilt and innocence.Ultimately, this study underscores the role of presupposition analysis as a tool in forensic linguistics for uncovering implicit meaning and assessing the fairness of language in legal discourse.